An innovative General Practice based Pharmacy Longitudinal Clerkship: using theory to characterise its development, implementation and initial evaluation. Issue 3 (4th May 2022) - Innes, Catriona; Rushworth, Gordon; Addison, Brian; Wedekind, Yvonne; Watson, Emma; Rudd, Ian; Power, Ailsa; Cunningham, Scott
ABSTRACT: Background: Longitudinal Integrated Clerkships exist in undergraduate medicine courses. A pilot Pharmacy Longitudinal Clerkship (pPLC) was funded to investigate delivery of this model of clinical education for student pharmacists. Objective(s): To investigate the development, implementation and initial evaluation of a pPLC. Methods: The 11-week pPLC was delivered to two students in two GP practices in Scotland. Mixed theory-based methods were used to gather information on the pPLC structures and processes required and qualitative semi-structured Theoretical Domains Framework (TDF) based interviews explored outcomes with key stakeholders. Informed written consent was obtained. Interviews were audio-recorded, transcribed verbatim and analysed thematically. University Ethics approval was granted. Results: Data were generated on resources and processes required for a pPLC including funds budgeted for and actually spent on staffing, student travel/subsistence and student clinical 'Kit Bags', learning outcomes, curriculum and training timetable, GP Practice/University contracts. Interviews were completed with the two students, three linked GP clinical supervisors and two Regional Tutors involved. The seven themes were identified and mapped to seven TDF domains including: increased levels of student confidence, and increased student enthusiasm for a career in pharmacy, need for definition of the role of the Regional Tutor for the PLC and GP positivity towards the expected outcomes of clerkship model versus traditional placements. Conclusion: Findings are limited by the small number of participants and settings, but evaluation was positive and the work garnered information on requirements for resources and processes. This will inform 'roll out' of the PLC.